Perancangan Infrastruktur Jaringan Untuk Block Situs Menggunakan Fitler Rules dan Address List di PT Dijital Generasi Kreasi - Junius Daniel; Muhamad Hadi Arfian (Universitas Batanghari Jambi, 2026)
This study aims to design and implement a network infrastructure using Filter Rules and Address List on a MikroTik Router to block access to sites that make employees unproductive in working at PT. Digital Generasi Kreasi. The development method used is the Network Development Life Cycle (NDLC) which consists of six stages: analysis, design, simulation prototype, implementation, monitoring, and management. The results of the study concluded that the application of the NDLC method to this network system is able to increase the efficiency of internet use, maintain network performance, and support employee productivity in the work environment.